FORMATION OF STUDENTS’ ENVIRONMENTAL AWARENESS UNDER THE CONDITIONS OF CONTEMPORARY CHALLENGES BY MEANS OF LITERARY FICTION ABOUT CHORNOBYL - Trukhan, Oksana (Mountain School of Ukrainian Carpaty, 2022)
The article deals with the problem of students’ environmental awareness formation under the conditions of contemporary challenges. It is noted that this problem is especially relevant for Ukraine under the conditions of the Russian- Ukrainian war. The Russian occupiers are organizing a terrible genocide of Ukrainians, destroying infrastructure, natural resources, the environment, and creating a threat of chemical and nuclear pollution as a result of shelling of military, industrial infrastructure, and chemical enterprises, warehouses of ammunition, petroleum products, airports, civil facilities, thermal, electrical, and nuclear power plants, including the Chornobyl NPP, etc. The great responsibility for the environment and the future gene pool of the Ukrainian nation rests not only on state structures, but also on teachers, the family, the public, the church and other factors. It is emphasized that the way to environmental awareness lies through effective environmental education, through the environmentalization of students’ consciousness. Therefore, it is time to reorient the content of the education system in the dimension of sustainable development, which involves, first of all, its environmentalization - the development of ecological thinking as a condition for the formation of ecological consciousness of the individual, acquiring of ecological knowledge, formation of ecological behaviour. The theoretical principles of education seekers’ environmental awareness formation through the prism of contemporary challenges are substantiated (the Russian-Ukrainian war and its consequences, environmental crisis phenomena and threats caused by the full-scale invasion of Russia into the territory of Ukraine, the Chornobyl disaster, etc.). Contemporary fiction about Chornobyl as a factor in the formation of environmental consciousness of the individual is analyzed. The Ukrainian and world Chornobyl literature discourse is singled out. It was concluded that works of fiction about Chornobyl are an important pedagogical tool that effectively influences the formation of the environmental consciousness of students, capable of expanding not only their ecological knowledge (the history of the Chornobyl disaster, its causes, consequences, etc.), but also the formation of ecological value attitudes (thrifty to nature) as the basis of the nature-centric character of ecological consciousness. Literary pieces of Chornobyl discourse also help to form ecologically appropriate behaviour (ecocentric type of ecological consciousness), as well as to cultivate a sense of patriotism, national dignity, historical memory, etc.